A Study on User-Oriented Subjects of Child Abuse on Wikipedia: Temporal Analysis of Wikipedia History Versions and Traffic Data - Yanyan Wang; Jin Zhang (JMIR Publications, 2023)
BackgroundMany people turn to online open encyclopedias such as Wikipedia to seek knowledge about child abuse. However, the information available on this website is often disorganized and incomplete. ObjectiveThe aim of this study is to analyze Wikipedia's coverage of child abuse and provide a more accessible way for users to browse child abuse-related content. The study explored the main themes and subjects related to child abuse on Wikipedia and proposed a multilayer user-oriented subject schema from the general users' perspective. MethodsThe knowledge of child abuse on Wikipedia is presented in the child abuse-related articles on it. The study analyzed child abuse-related articles on Wikipedia, examining their history versions and yearly page views data to reveal the evolution of content and popularity. The themes and subjects were identified from the articles' text using the open coding, self-organizing map, and n-gram approaches. The subjects in different periods were compared to reveal changes in content. ResultsThis study collected and investigated 241 associated Wikipedia articles and their history versions and traffic data. Four facets were identified: (1) maltreatment behavior (n=118, 48.9%); (2) people and environment (n=28, 11.6%); (3) problems and risks (n=33, 13.7%); and (4) protection and support (n=62, 25.7%). A total of 8 themes and 51 subjects were generated from the text, and a user-oriented subject schema linking the facets, themes, subjects, and articles was created. Maltreatment behavior (number of total views = 1.15 × 108) was the most popular facet viewed by users, while people and environment (number of total views = 2.42 × 107) was the least popular. The popularity of child abuse increased from 2010 to 2014 but decreased after that. ConclusionsThe user-oriented subject schema provides an easier way for users to seek information and learn about child abuse. The knowledge of child abuse on Wikipedia covers the harms done to children, the problems caused by child abuse, the protection of children, and the people involved in child abuse. However, there was an inconsistency between the interests of general users and Wikipedia editors, and the child abuse knowledge on Wikipedia was found to be deficient, lacking content about typical child abuse types. To meet users' needs, health information creators need to generate more information to fill the knowledge gap.